Jogos educacionais: as ferramentas analíticas como potencial de validação de aprendizado - Ortiz, Julio Cesar Martins (2023)
This work will demonstrate the efficiency of Analytics in an educational software produced by us, proving that a digital game with educational purposes can generate promising results and assisting in student learning while providing analysis data to the teacher/tutor. We will initially address the state of the art in item 4, exploring research carried out by other authors in different areas of study to analyze the result of this research, showing why this combination of digital games with the educational model is positive, progressing to an analysis of research in item 5 and then a case study in item 6, this being a comparison between a State of the Art research and our research. In item 7 we will discuss why we selected a research work that is close to ours. In item 8 we will have an explanation of why Analytics is useful in digital games and its relationship with our research. With this, item 9 will show some experiments carried out by us to complete the research in item 10